Overview of biotechnology - Meridian Education Corporation (New Jersey : Meridian Education Corporation, 2004)
Some of the hottest challenges facing the 21st century are being worked on right now by biotechnologists. This introductory-level program investigates the dynamic field of biotechnology and examines how it relates to a cross-section of different disciplines such as medicine, healthcare, ergonomics, and communications. In addition, employees from the biotechnology sector offer their insights on the work that they do and on the industry as a whole.
Keywords: Genetics; Heredity, Human